FINANCIAL BEHAVIOR ON FINANCIAL SATISFACTION AND PERFORMANCE OF THE INDONESIAN BATIK INDUSTRY - Sumani, Sumani; Awwaliyah, Intan Nurul; Suryaningsih, Ika Barokah; Nurdin, Djayani (Jurnal Aplikasi Manajemen, 2022)
The urgency of the research is that many business people understand financial literacy but seem to have less impact on financial performance. It is probably because some business people have not followed up with changes in good financial behavior. This study aims to determine the effect of financial literacy on financial behavior, financial satisfaction, and financial performance. In addition, it also knows the effect of financial behavior on financial satisfaction and financial performance and the effect of financial satisfaction on financial performance. The population in this study is the entire batik industry in Indonesia with large and medium scale, as many as 208 batik business actors. The sampling technique is a saturated sample or census, where all members of the population become members of the sample. The data analysis technique used SMART PLS 03 software. According to the study's findings, financial literacy has a significant effect on financial behavior and financial performance, and financial behavior significantly affects financial satisfaction. Financial satisfaction furthermore has a significant effect on financial performance. However, financial literacy has no effect on financial satisfaction, and financial behavior has also been found to have no effect on financial performance. This research implies that the financial performance of batik industry players will increase if they have financial behavior that can create added value and the importance of financial literacy.